2015
DOI: 10.4238/2015.november.13.22
|View full text |Cite
|
Sign up to set email alerts
|

Effects of muscle fiber type on glycolytic potential and meat quality traits in different Tibetan pig muscles and their association with glycolysis-related gene expression

Abstract: ABSTRACT. The myosin heavy chain (MyHC) composition, glycolytic potential, mitochondrial content, and gene expression related to energy metabolism were analyzed in eight muscles from Tibetan pigs, to study how meat quality develops in different muscle tissues. The muscles were classified into three clusters, based on MyHC composition: masseter, trapezius, and latissimus dorsi as 'slow-oxidative-type'; psoas major and semimembranosus as 'intermediate-type'; and longissimus dorsi, obliquus externus abdominis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 36 publications
4
23
0
2
Order By: Relevance
“…For example, HK-2 , a key gene involved in these processes, plays an important role in encoding the first rate-limiting enzyme catalyzing the glycogen degradation reaction through glycolysis. It has previously been reported that HK-2 is positively correlated with glycolytic potential and is less strongly expressed in slow-oxidative-type muscle49, a result consistent with the present findings that the high methylation status of HK-2 resulted in lower mRNA expression levels in PMM (Fig. 5c).…”
Section: Resultssupporting
confidence: 93%
“…For example, HK-2 , a key gene involved in these processes, plays an important role in encoding the first rate-limiting enzyme catalyzing the glycogen degradation reaction through glycolysis. It has previously been reported that HK-2 is positively correlated with glycolytic potential and is less strongly expressed in slow-oxidative-type muscle49, a result consistent with the present findings that the high methylation status of HK-2 resulted in lower mRNA expression levels in PMM (Fig. 5c).…”
Section: Resultssupporting
confidence: 93%
“…Similar experiments have been carried out on other fish species, with the anaerobic metabolism found to accelerate with increasing muscle hardness in Atlantic salmon48. In addition, the glycolytic pathway has also been investigated in pork of different qualities, revealing that the expression of glyceraldehyde-3-phosphate dehydrogenase and lactate dehydrogenase is significantly increased in pork with a hard texture49. However, the specific mechanism of the glycolytic metabolic pathway during muscle hardening remains to be elucidated.…”
Section: Discussionmentioning
confidence: 59%
“…Based on findings of other authors indicating relations of histological structure and meta quality and carcass traits [ 10 12 ], we also performed an association study on a large number of pigs. For this analysis four genes were selected: TNNT2 ; FOXO1 ; TACC2 ; DEGS1 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been well-established that percentage number of fiber types in muscle determines metabolic properties and water holding capacity of muscle tissue, as well as marbling, intramuscular fat (IMF) level, meat color and texture [ 10 12 ]. In our previous study performed on Large White pigs, we identified genes differentially expressed in muscle contingent on histological microstructure [ 13 ].…”
Section: Introductionmentioning
confidence: 99%